ANALISIS DAMPAK RENOVASI FASILITAS PANTAI SALIPER ATE TERHADAP PENDAPATAN MASYARAKAT KABUPATEN SUMBAWA - Erlis Mawaddah; Novi Kadewi Sumbawati; Rosyidah Rachman (Jurnal Ekonomi & Bisnis, 2023)
The purpose of this research was to determine the impact of the renovation of the Saliperate beach facility on the income of the people of Sumbawa Regency. This type of research is a comparative research that aims to compare people's income before and after the renovation of the Saliper Ate Beach facility. The type of data used is quantitative data in the form of community income data before and after the renovation of the Saliper Ate Beach facility which was obtained directly using the interview method. This research is a population study, in which researchers take the entire population of 21 people as the research sample. Data analysis was carried out by means of different test techniques, including paired samples statistics test, paired samples correlations test, and paired samples t-test. The results showed that there were differences between the income levels of the people in Sumbawa Regency before and after the renovation of the Saliper Ate Beach facility. The renovation of the Saliper Ate Beach facility has had a positive impact on people's income in Sumbawa Regency. The average amount of income earned by the community after the renovation of the Saliper Ate Beach facilities has increased compared to the income earned before the renovation of the Saliper Ate Beach facilities.